ChemInform Abstract: A Base‐Controlled Chemoselective Transfer Hydrogenation of α, β‐Unsaturated Ketones Catalyzed by [IrCp*Cl2]2 with 2‐Propanol. Issue 27 (18th June 2015) - Chen, Shu‐jie; Lu, Guo‐ping; Cai, Chun
Abstract Depending on the base, a wide range of α, β‐unsaturated ketones are reduced to saturated ketones or alcohols by using a simple homogeneous catalytic system based on the commercially available Iridium catalyst under optimized reaction conditions.